LEARNING ENGLISH THROUGH ECOTOURISM: STUDENTS’ EXPERIENCES, LINGUISTIC DEVELOPMENT, AND ENVIRONMENTAL RESPONSIBILITY IN EFL - Fatma Setya Ningrum; Meutya Rizki Ramadhani; Destina Kasriyati (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
As sustainability challenges reshape educational priorities worldwide, English Language Teaching (ELT) is increasingly expected to promote not only language development but also environmental responsibility. Although sustainability-oriented ELT and ecotourism-based learning have received growing scholarly attention, previous studies have mainly focused on pedagogical models, curriculum integration, and teacher perspectives, while learners’ experiences remain underexplored, particularly in Indonesian higher education. Addressing this gap, this study investigates students’ learning experiences in ecotourism-based English learning and examines how engagement with ecotourism topics influences their linguistic development and environmental responsibility. Using a qualitative descriptive design, the study involved six undergraduate students from the English Education Study Program at Universitas Lancang Kuning who had completed the English for Eco Edu Tourism course. Data were collected through semi-structured interviews and analyzed using Braun and Clarke’s thematic analysis. Four themes emerged: meaningful learning experiences, linguistic development, linguistic challenges, and environmental responsibility. Participants perceived ecotourism as an authentic context for learning English that supported vocabulary development, communication skills, and meaningful language use. They also reported challenges related to unfamiliar terminology, pronunciation, and confidence in expressing ideas. Furthermore, engagement with ecotourism topics strengthened students’ awareness of conservation and responsible tourism practices. These findings provide learner-centered evidence supporting ecotourism-based instruction as an effective approach for integrating language development with environmental responsibility in EFL contexts.